Contribution of the in-vehicle microenvironment to individual ambient-source nitrogen dioxide exposure: the Multi-Ethnic Study of Atherosclerosis and Air Pollution - Hazlehurst, Marnie F. (J Expo Sci Environ Epidemiol, 2018)
Exposure estimates that do not account for time in-transit may underestimate exposure to traffic-related air pollution, but exact contributions have not been studied directly. We conducted two-week monitoring, including novel in-vehicle sampling, in a subset of the Multi-Ethnic Study of Atherosclerosis and Air Pollution cohort in two cities. Participants spent the majority of their time indoors and only 4.4% of their time (63 min/day) in-vehicle, on average. The mean ambient-source NO(2) concentration was 5.1 ppb indoors and 32.3 ppb in-vehicle during drives. On average, indoor exposure contributed 69% and in-vehicle exposure contributed 24% of participants’ ambient-source NO(2) exposure. For participants in the highest quartile of time in-vehicle (≥1.3 hrs/day), indoor and in-vehicle contributions were 60% and 31%, respectively. Incorporating infiltrated indoor and measured in-vehicle NO(2) produced exposure estimates 5.6 ppb lower, on average, than using only outdoor concentrations. The indoor microenvironment accounted for the largest proportion of ambient-source exposure in this older population, despite higher concentrations of NO(2) outdoors and in vehicles than indoors. In-vehicle exposure was more influential among participants who drove most and for participants residing in areas with lower outdoor air pollution. Failure to characterize exposures in these microenvironments may contribute to exposure misclassification in epidemiologic studies.